THE PEDAGOGICAL NECESSITY OF A SYSTEM FOR DEVELOPING CREATIVE COMPETENCE IN FUTURE TECHNOLOGY TEACHERS FOR PROFESSIONAL ACTIVITY - Avazov G’oyibnazar Berdiyevich (Modern American Journals, 2025)
In the modern education system, creativity and innovative thinking skills play a vital role in the professional activities of teachers. Future technology teachers must possess creative competence, particularly in introducing students to modern technologies and teaching them to think innovatively. This article discusses the pedagogical necessity of a system for developing creative competence in the preparation of future technology teachers for their professional activities.
Keywords: technology, pedagogical skills, innovative solutions, innovative thinking, creative competence, modern education system, creative thinking.